Stakeholders and the duty to act in the best interests of the company: what is required of directors? - Kemp, Courtney Kirsten (Department of Commercial Law, 2022)
This dissertation explores the content of the fiduciary duty of a company director to act in ‘the best interests of the company' as expressed in the common law and section 76(3)(b) of the Companies Act 71 of 2008. The central contention is whether the duty is owed to shareholders or otherwise to stakeholders and if the latter, to what extent. The content of and approach favoured in the present duty is analysed first through a discussion of theories on corporate governance, personality and social responsibility. This provides theoretical context. A thorough analysis of the common law follows. This provides evidence of the development of the duty to act in the best interests of the company and the policy choices which may be implied from those developments. That analysis concludes that the duty means that directors shall perform their functions to the benefit of ‘the company.' The common law provides that ‘the company' has developed to mean the shareholders as a whole but not necessarily exclusively or primarily. Since the duty to act in the best interests of the company is largely open to interpretation in accordance with the policy of the time, this dissertation proceeds with a discussion of the influence of the Constitution and the value of ubuntu on the duty. The conclusion is that even in the constitutional era, the fiduciary duty requires little more than a consideration – and not a championing – of stakeholder interests. Ultimately, the duty to act in the best interests of the company is ambiguous. Directors may be uncertain of what standard the law expects of them in exercising their decision-making power. Given this uncertainty, a discussion of the business judgment rule is necessary. The business judgment rule requires rationality from directors if they are to avoid liability. The rule is therefore crucial to informing what standard of conduct is expected of directors.